2020
DOI: 10.1111/jnc.15251
|View full text |Cite
|
Sign up to set email alerts
|

The cGMP system in normal and degenerating mouse neuroretina: New proteins with cGMP interaction potential identified by a proteomics approach

Abstract: The hereditary disease Retinitis pigmentosa results in severe vision loss due to photoreceptor degeneration by unclear mechanisms. In several disease models, the second messenger cGMP accumulates in the degenerating photoreceptors, where it may over‐activate specific cGMP‐interacting proteins, like cGMP‐dependent protein kinase. Moreover, interventions that counteract the activity of these proteins lead to reduced photoreceptor cell death. Yet there is little or no information whether other than such regular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…This method was optimized in a previous study (Rasmussen et al, 2020). In brief, a sample of the soluble cortex fraction [1.5 mg] was added to 60 µl of following cGMP agaroses: 8-AET-cGMP, 2-AH-cGMP, 2′-AHC-cGMP, Sp-8-AET-cGMPS, Sp-2′-AHC-cGMPS, Rp-8-AET-cGMPS, Rp-2′-AHC-cGMPS, or EtOH-NH, respectively, with 500 µl PBS [0.137 m NaCl, 2.7 mm KCl, 10 mm Na 2 HPO 4 , and 1.8 mm KH 2 PO 4 ].…”
Section: Affinity Pull Downmentioning
confidence: 99%
See 2 more Smart Citations
“…This method was optimized in a previous study (Rasmussen et al, 2020). In brief, a sample of the soluble cortex fraction [1.5 mg] was added to 60 µl of following cGMP agaroses: 8-AET-cGMP, 2-AH-cGMP, 2′-AHC-cGMP, Sp-8-AET-cGMPS, Sp-2′-AHC-cGMPS, Rp-8-AET-cGMPS, Rp-2′-AHC-cGMPS, or EtOH-NH, respectively, with 500 µl PBS [0.137 m NaCl, 2.7 mm KCl, 10 mm Na 2 HPO 4 , and 1.8 mm KH 2 PO 4 ].…”
Section: Affinity Pull Downmentioning
confidence: 99%
“…The cGMP's effector proteins elicit a broad variety of cellular functions (Schlossmann & Schinner, 2012) and include PKG and PKA (Huang et al, 2014;Kim, Zhong, et al, 2016;Reed et al, 1996) (which phosphorylate downstream target proteins), cyclic nucleotidegated channels (Altenhofen et al, 1991) (CNGs, that upon stimulation allow cation fluxes), and the regulatory PDEs (Yan et al, 1996) (responsible for abrogating the cGMP signaling). However, also other proteins may bind to cGMP (Rasmussen et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies identified additional cGMP-interacting proteins such as PKAs, PKCs, and CaMKs as upregulated in IRD retinas, which might be interesting in developing new therapeutic targets (49,50). These recent findings corresponded well with our study where we also identified these same kinases as activated in rd1 diseased retinal explants and inhibited by the PKG inhibitor, CN03.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified additional cGMP-interacting proteins such as PKAs, PKCs, and CaMKs as upregulated in IRD retinas, which might be interesting in developing new therapeutic targets (49,50).…”
Section: Pkg Inhibition and Peptide Microarray Technology For The Prediction Of Pkg Phosphorylation Targetsmentioning
confidence: 99%